Performance Management in State Universities in Cameroon: An Administrator’s Perspective - Ntui, Agbor Michael (International Journal of Educational Studies, 2018)
This study provides an in-depth understanding of how administrators perceive the purpose and value of the performance management systems in state Universities of Cameroon; how the administrator assess the effectiveness of current performance management processes in the department; the different dimensions of how administrators perceive the impact of academic managers on their work performance; the extent to which administrators respond to the process, measure and outcomes involved in operating the performance management system. The study also analyzes what administrators think is an effective performance management system in the state Universities. The research adopted a qualitative case study approach by selecting 12 administrators from 6 state Universities with varied backgrounds in terms of years of service, seniority and gender. Data were collected through in-depth, semi- structured interviews and documentary sources. Among the major findings were that the participants found the meaning and purposes of performance management ambiguous; and that the many different processes contained within the system were perceived as fragmenting and confusing in achieving the intended outcomes. Compounding the concern was the lack of dedicated and able academics to manage the process.